Effects on human heart valve immunogenicity in vitro by high concentration cryoprotectant treatment. (7th June 2017) - Högerle, Benjamin A.; Schneider, Maria; Sudrow, Katrin; Souidi, Naima; Stolk, Meaghan; Werner, Isabella; Biermann, Anna; Brockbank, Kelvin G.M.; Stock, Ulrich A.; Seifert, Martina
Abstract: It has been shown previously that cryopreservation, using an ice‐free cryopreservation method with the cryoprotectant formulation VS83, beneficially modulated immune reactions in vivo and in vitro when compared with conventionally frozen tissues. In this study, we assessed the impact of a VS83 post‐treatment of previously conventionally frozen human tissue on responses of human immune cells in vitro . Tissue punches of treated and non‐treated (control) aortic heart valve tissue (leaflets and associated aortic root) were co‐cultured for 7 days with peripheral blood mononuclear cells or enriched CD14 + monocytes. Effects on cellular activation markers, cytokine secretion and immune cell proliferation were analysed by flow cytometry. Flow cytometry studies showed that VS83 treatment of aortic root tissue promoted activation and differentiation of CD14 + monocytes, inducing both up‐regulation of CD16 and down‐regulation of CD14. Significantly enhanced expression levels for the C‐C chemokine receptor (CCR)7 and the human leukocyte antigen (HLA)‐DR on monocytes co‐cultured with VS83‐treated aortic root tissue were measured, while the interleukin (IL)‐6 and monocyte chemoattractant protein (MCP)‐1 release was suppressed. However, the levels of interferon (IFN)γ and tumour necrosis factor (TNF)α remained undetectable, indicating that complete activation into pro‐inflammatory macrophages did not occur. Similar, but non‐significant, changes occurred with VS83‐treated leaflets. Additionally, in co‐cultures with T cells, proliferation and cytokine secretion responses were minimal. In conclusion, post‐treatment of conventionally cryopreserved human heart valve tissue with the VS83 formulation induces changes in the activation and differentiation characteristics of human monocytes, and thereby may influence long‐term performance following implantation. Copyright © 2017 John Wiley & Sons, Ltd.